Resetting parameters in Chinese speakers' acquisition of Korean wh-phrase with [±Q] feature - Park, Sun Hee; Jeong, Jin; Kim, Hyunwoo (Linguistic research, 2021)
This study investigated whether Chinese speakers can acquire features associated with the embedded wh-phrase in Korean. Researchers have made different predictions regarding L2 parameter resetting. Some approaches claim that L1 parameter values can be successfully reset to L2-specific values, whereas others predict consistent difficulty in L2 parameter resetting. Our analyses of an acceptability judgment task showed that despite the lack of relevant information in their L1, Chinese-speaking learners of Korean had target-like knowledge of the morphological constraints associated with the features that license wh-phrases in Korean embedded clauses. We also found that learner performance was modulated by their Korean proficiency. These findings align with the view that parameter resetting is possible in L2 acquisition insofar as L2 proficiency is sufficiently high.